Manajemen Risiko dalam Meningkatkan Mutu Pendidikan di MTs Muhammadiyah Sanden - Rosyada, Ita; Setiawan, Farid; Rimadhani, Mira Ifta; Rohmadani, Adinda Icha (MASALIQ, 2022)
Risk is something that always exists in human life, whether it is in the activities carried out by humans, an organization, an institution, a company, and even a government. Risk is usually considered as an adverse event, therefore we as humans need to be careful and make the right calculations in everything. However, when we are careful and run according to the plan, but we experience losses / are still affected by these risks. With this, risk management is needed, as an effort to always be able to survive in the face of all risks in various unpredictable circumstances. The author uses a qualitative method, obtaining information through interviews with the Principal of Mts Muhammadiyah Sanden, as well as from various literatures. The purpose of this study was to determine the role of risk management in improving the quality of education at Mts Muhammadiyah Sanden, through the process of program evaluation, implementation evaluation, and evaluation of activity results. This is very influential and runs smoothly in improving the quality of schools, because in managing its activities it is very good and can minimize the risks of its activities.